Pengabdian Masyarakat PKM TINGKAT PENGETAHUAN SERTA PENGAPLIKASIAN WARMING UP DAN COOLING DOWN DENGAN ANGKA KEJADIAN CEDERA PADA ATLET SILAT PPLP JAWA TENGAH - Triyanita, Maya; Pambudi, Restu Arya (IFI cabang Kota Bekasi, 2024)
importance of warming up and cooling down before and after carrying out sports activities for Central Java PPLP silat athletes. Physical fitness is a need that must be met so that we can carry out daily life activities well. Another definition, physical fitness is the body's ability to carry out activities without experiencing excessive fatigue. If warming up helps our body make the transition from a state of rest to moderate activity, then cooling down makes it relax and calm again after the body has carried out training or competition activities. To determine the level of heating and cooling knowledge, it can be measured using a questionnaire. This service aims to share knowledge with athletes about what a warm-up and cool-down is so that it can reduce the incidence of injuries in Central Java PPLP martial arts athletes.